Self-repairing asphalt pavement material and preparation method thereof
By adding components such as repaired hollow fibers to the asphalt pavement materials, the self-repair function of releasing repair agents to fill cracks at high temperatures is achieved, solving the problems of aging and microcracks of existing asphalt pavements, and improving the durability and service life of the material.
Patent Information
- Application Number
- CN202510211944.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-29
AI Technical Summary
Existing asphalt pavement is prone to diseases such as aging and microcracks during long-term use, resulting in reduced safety, shortened service life and increased maintenance costs. Traditional repair methods are inefficient and costly.
A self-repaired asphalt pavement material is used, which includes matrix asphalt, repaired hollow fibers, silicate nanoparticles, natural mineral fillers, polyvinylidene fluoride and crude aggregates, which fill cracks by releasing repair agents at high temperatures and extend service life.
The material has excellent mechanical properties and durability, and has good self-repair ability. It can effectively fill cracks under temperature changes or external forces, extend the service life of the road, and reduce maintenance costs.
Smart Images

Figure BDA0005286239070000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to a self-repairing asphalt pavement material and a preparation method thereof. Background Art
[0002] Asphalt is widely used in road construction due to its low cost, corrosion resistance, temperature sensitivity and good adhesion. However, in the long-term use, asphalt pavement will inevitably be affected by factors such as light, oxygen, temperature changes, humidity and the volatilization of its own oil, resulting in aging and micro cracks. These diseases not only affect the appearance of the road surface, but more importantly, reduce the safety and service life of the road surface and increase maintenance costs.
[0003] Traditional repair methods usually rely on manual intervention, such as patching cracks and resurfacing the road surface. This method is not only costly but also inefficient and cannot meet the needs of modern traffic construction and management. Therefore, the development of a new type of asphalt pavement material that can self-repair, extend its service life and reduce maintenance costs has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the above problems, the present application provides a self-repairing asphalt pavement material and a preparation method.
[0005] In the first aspect, the present application provides a self-repairing asphalt pavement material, which adopts the following technical solution: A self-repairing asphalt pavement material, comprising the following raw materials in parts by weight: 20-24 parts of matrix asphalt, 8-10 parts of repair hollow fibers, 2-4 parts of silicate nanoparticles, 10-15 parts of natural mineral fillers, 8-10 parts of polyvinylidene fluoride, and 80-120 parts of coarse aggregate.
[0006] By adopting the above technical solutions, the asphalt pavement material produced not only has excellent mechanical properties and durability, but also has good self-repairing ability. Among them, the matrix asphalt, as the main binder, provides basic bonding and load-bearing capacity; the repair-type hollow fiber introduces a self-repairing mechanism, which can release the internal repair agent when the temperature changes, fill the cracks, and extend the service life of the road. Silicate nanoparticles enhance the mechanical strength and thermal stability of the material, natural mineral fillers increase the density and compressive strength of the mixture, and polyvinylidene fluoride gives the material better weather resistance and corrosion resistance. Natural mineral fillers and coarse aggregates as aggregates ensure the structural stability and load-bearing capacity of the pavement material, so that the entire material system can maintain good performance in various environments.
[0007] Optionally, the repairable hollow fiber uses polyvinyl butyral and polyhexamethylene terephthalamide as wall materials and an asphalt repair agent as core material, and is obtained through a dry-wet spinning process.
[0008] By adopting the above technical solution, asphalt pavement is prone to cracking under high temperature environment. To solve this problem, polyvinyl butyral (PVB) is introduced as the wall material of the repair material. PVB will soften and deform at high temperature, causing the repair material contained in the hollow fiber to seep out and effectively fill the small cracks in the road surface. When the temperature drops, PVB hardens again, giving the asphalt better thermal stability and mechanical properties.
[0009] Furthermore, when the asphalt is subjected to a large external force and microcracks are generated, the hollow fiber will also break due to the force, prompting the repair agent contained therein to quickly gush out to cope with the formation of cracks. The use of polyvinyl butyral and poly (hexamethylene terephthalamide) (PA6T) as fiber wall materials not only provides good mechanical strength and flexibility, but also gives the fiber temperature responsiveness. The combination of these two materials can maintain a stable structural morphology at room temperature, and under high temperature conditions, the fiber can soften and release the internal repair agent, thereby giving full play to the self-repair function.
[0010] Optionally, the preparation of the repaired hollow fiber comprises the following steps: (1) polyvinyl butyral is placed in a dichloromethane solvent and stirred to dissolve, a dithiol compound is added to the above solution and stirred until uniformly dispersed, a poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide is added and stirred uniformly, and then placed in a vacuum oven at 55-65° C. for defoaming for 22-24 hours to obtain a casting solution; (2) The casting liquid is extruded and spun under the action of high-pressure nitrogen to form a hollow fiber shape. During this process, the asphalt repair agent is pressurized into the cavity of the hollow fiber as an internal coagulation liquid to serve as a support, and the fiber end is sealed. It is immersed in water to coagulate and form, and after drying, a 2-3 cm repaired hollow fiber is formed.
[0011] By adopting the above technical solution, the addition of dithiol compounds achieves thermally reversible crosslinking, allowing the fiber to release the repair agent at high temperature and return to its original state after cooling, thus extending the validity period of the repair mechanism. High-pressure nitrogen extrusion spinning ensures the uniformity and integrity of the fiber, while the introduction of the internal coagulation liquid ensures the stability of the fiber's internal structure and the effective filling of the repair agent. The final 2-3cm long fiber helps to be evenly distributed in the pavement material, improves the repair effect of the hollow fiber, and ensures that the self-repair function can be effectively exerted in practical applications.
[0012] Optionally, the preparation process of the repairable hollow fiber includes the following raw materials in parts by weight: 6-8 parts of polyvinyl butyral, 18-20 parts of dichloromethane solvent, 0.5-2 parts of dithiol compound, 14-16 parts of polyhexamethylene terephthalamide solution, and 16-20 parts of asphalt repair agent.
[0013] Optionally, 0.5-3 parts of nano-silicon dioxide are also added to the repaired hollow fiber.
[0014] By adopting the above technical solution, the addition of nano-silicon dioxide significantly improves the mechanical strength and wear resistance of the fiber, while enhancing the thermal and chemical stability of the material. This enables the fiber to maintain excellent performance under complex environmental conditions.
[0015] Optionally, the repair agent includes 8-10 parts of water-based epoxy resin, 60-70 parts of solvent oil and 10-15 parts of carboxylated styrene-butadiene latex.
[0016] By adopting the above technical solutions, the synergistic effect of different components ensures its effectiveness and adaptability in various environmental conditions. Water-based epoxy resin provides strong adhesion and durability, which can effectively fill cracks and enhance the structural stability of the material. Solvent oil helps other components to dissolve better and promote their penetration into the asphalt pavement, improves the fluidity of the repair agent, and makes it easier to enter small cracks and pores. Carboxylated styrene butadiene latex increases the flexibility and adhesion of the material, making the repair layer more solid and less likely to peel off. This combination not only improves the repair effect of the material, but also extends the service life of the repair layer and reduces the need for subsequent maintenance.
[0017] Optionally, the natural mineral filler is limestone powder.
[0018] By adopting the above technical solution, limestone powder can effectively fill the gaps in asphalt pavement materials, thereby improving the density of the materials. Secondly, limestone powder can also reduce the internal friction between the raw material particles of the pavement materials, which helps to further enhance the structural stability of the materials. Through the filling effect and chemical adsorption, limestone powder makes the internal structure of the material more dense and firm, and improves the compressive strength.
[0019] In a second aspect, the present application provides a method for preparing a self-repairing asphalt pavement material, using the following technical solution: A method for preparing a self-repairing asphalt pavement material comprises the following steps: S1: heating the base asphalt to 150-180° C., adding the natural mineral filler, silicate nanoparticles, polyvinylidene fluoride and coarse aggregate, stirring and mixing well to obtain a mixture; S2: Add the repairable hollow fiber into the mixture and stir it at high speed for 30-60 minutes at a stirring speed of 3500-4000 r / min to obtain the self-repairing asphalt pavement material.
[0020] In summary, this application has the following beneficial effects: 1. Since the present application uses matrix asphalt as the main binder and adds silicate nanoparticles, natural mineral fillers and polyvinylidene fluoride and other ingredients, the mechanical strength and durability of the material are significantly improved. These ingredients work together to enable the pavement material to maintain stable performance when subjected to harsh conditions such as heavy loads and high temperatures, ensuring the safety and reliability of the road.
[0021] 2. In the present application, repairable hollow fibers are preferably added, with polyvinyl butyral and poly(hexamethylene terephthalamide) as wall materials. The pavement material can release internal repair agents under temperature changes or external forces, effectively fill cracks, achieve self-repair, and effectively improve the material's aging resistance. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0024] SK-90 base asphalt has a needle penetration of 94.5 mm, a softening point of 47.3 °C, and a density of 1.004 g / cm 3 , ductility at 15℃ is greater than 150; water-based epoxy resin was purchased from Zhonghe Chemical (Shandong) Co., Ltd., model E51128; carboxylated styrene butadiene latex was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., model: 25085-39-6; coarse aggregate is a continuous gradation of granite crushed stone with a particle size of 5-25mm and a crushing value of 10.0%; the particle size of silicate nanoparticles is 50-80nm.
[0025] Preparation examples of raw materials and / or intermediates Preparation Example 1 A repaired hollow fiber, the preparation of which comprises the following steps: (1) 6 kg of polyvinyl butyral was placed in a dichloromethane solvent and stirred to dissolve, 1 kg of tetraethylene glycol dimercaptopropionate (dithiol compound) was added to the above solution and continued to stir until uniformly dispersed, 16 kg of a poly(hexamethylene terephthalamide) solution with a mass concentration of 10% pre-dissolved in dimethylformamide was added and stirred evenly, and then placed in a vacuum oven at 60° C. for 24 hours to defoam to obtain a casting solution; (2) 9 kg of water-based epoxy resin, 65 kg of No. 90 solvent oil and 12.5 kg of carboxylated styrene-butadiene latex were mixed to prepare a repair agent; (3) Pour the defoamed casting liquid into a spinning tank maintained at 60°C, turn on the high-pressure nitrogen system, set the pressure to 0.15MPa, and extrude the casting liquid through a spinneret to form a hollow fiber shape. In this process, 16kg of repair agent is used as an internal coagulation liquid and flows through a rotor flowmeter at a pressure of 0.2MPa into the cavity of the hollow fiber as a support to seal the fiber end. After the fiber is slightly shaped in the air, it is placed in water at 25°C for further coagulation and shaping. After being fished out and dried, a 2-3cm repaired hollow fiber is formed.
[0026] Preparation Example 2 A repaired hollow fiber, the preparation of which comprises the following steps: (1) 7 kg of polyvinyl butyral was placed in a dichloromethane solvent and stirred to dissolve, 0.5 kg of tetraethylene glycol dimercaptopropionate (dithiol compound) was added to the above solution and continued to stir until uniformly dispersed, 15 kg of a 10% poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide was added and stirred evenly, and then placed in a vacuum oven at 55° C. for 23 hours to defoam to obtain a casting solution; (2) 10 kg of water-based epoxy resin, 70 kg of No. 90 solvent oil and 10 kg of carboxylated styrene-butadiene latex were mixed evenly to prepare a repair agent; (3) Pour the defoamed casting liquid into a spinning tank maintained at 55°C, turn on the high-pressure nitrogen system, set the pressure to 0.15MPa, and extrude the casting liquid through a spinneret to form a hollow fiber shape. In this process, 20kg of repair agent is used as an internal coagulation liquid and flows through a rotor flowmeter at a pressure of 0.2MPa into the cavity of the hollow fiber as a support to seal the fiber end. After the fiber is slightly shaped in the air, it is placed in water at 25°C for further coagulation and shaping. After being fished out and dried, a 2-3cm repaired hollow fiber is formed.
[0027] Preparation Example 3 A repaired hollow fiber, the preparation of which comprises the following steps: (1) 8 kg of polyvinyl butyral was placed in a dichloromethane solvent and stirred to dissolve, 2 kg of tetraethylene glycol dimercaptopropionate (dithiol compound) was added to the above solution and continued to stir until uniformly dispersed, 14 kg of a 10% poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide was added and stirred evenly, and then placed in a vacuum oven at 65° C. for 22 hours to defoam to obtain a casting solution; (2) 8 kg of water-based epoxy resin, 60 kg of No. 90 solvent oil and 15 kg of carboxylated styrene-butadiene latex were mixed to prepare a repair agent; (3) Pour the defoamed casting liquid into a spinning tank maintained at 65°C, turn on the high-pressure nitrogen system, set the pressure to 0.15MPa, and extrude the casting liquid through a spinneret to form a hollow fiber shape. In this process, 18kg of repair agent is used as an internal coagulation liquid and flows through a rotor flowmeter at a pressure of 0.2MPa into the cavity of the hollow fiber as a support to seal the fiber end. After the fiber is slightly shaped in the air, it is placed in 25°C water for further coagulation and shaping. After being fished out and dried, a 2-3cm repaired hollow fiber is formed.
[0028] Preparation Example 4 A repaired hollow fiber, which is different from Preparation Example 1 in that only poly(hexamethylene terephthalamide) is used as the wall material of the hollow fiber in this Preparation Example, specifically comprises the following steps: (1) 1 kg of tetraethylene glycol dimercaptopropionate (dithiol compound) and 16 kg of a 10% poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide were mixed evenly, and then placed in a vacuum oven at 60° C. for defoaming for 24 hours to obtain a casting solution; (2) 9 kg of water-based epoxy resin, 65 kg of No. 90 solvent oil and 12.5 kg of carboxylated styrene-butadiene latex were mixed to prepare a repair agent; (3) Pour the defoamed casting liquid into a spinning tank maintained at 60°C, turn on the high-pressure nitrogen system, set the pressure to 0.15MPa, and extrude the casting liquid through a spinneret to form a hollow fiber shape. In this process, 16kg of repair agent is used as an internal coagulation liquid and flows through a rotor flowmeter at a pressure of 0.2MPa into the cavity of the hollow fiber as a support to seal the fiber end. After the fiber is slightly shaped in the air, it is placed in water at 25°C for further coagulation and shaping. After being fished out and dried, a 2-3cm repaired hollow fiber is formed.
[0029] Preparation Example 5 A repaired hollow fiber, which is different from Preparation Example 1 in that no dithiol compound is added in this Preparation Example, and the steps are as follows: (1) 6 kg of polyvinyl butyral was placed in a dichloromethane solvent and stirred to dissolve, 16 kg of a 10% poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide was added and stirred evenly, and then placed in a vacuum oven at 60° C. for 24 hours to defoam to obtain a casting solution; the remaining steps were the same as those in Preparation Example 1.
[0030] Preparation Example 6 A repaired hollow fiber, which is different from Preparation Example 1 in that 0.5 kg of nano-silicon dioxide is also added in this Preparation Example, specifically comprising the following steps: (1) 6 kg of polyvinyl butyral was placed in a dichloromethane solvent and stirred to dissolve, 1 kg of tetraethylene glycol dimercaptopropionate (dithiol compound) was added to the above solution and continued to stir until uniformly dispersed, 16 kg of a 10% poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide was added and stirred evenly, 0.5 kg of nano-silicon dioxide was added and dispersed evenly using ultrasound, and then placed in a vacuum oven at 60° C. for 24 hours to defoam to obtain a casting solution; the remaining steps were the same as those in Preparation Example 1.
[0031] Preparation Example 7 A repaired hollow fiber, which is different from Preparation Example 6 in that 2 kg of nano-silicon dioxide is added in this Preparation Example.
[0032] Preparation Example 8 A repaired hollow fiber, which is different from Preparation Example 6 in that 3 kg of nano-silicon dioxide is added in this Preparation Example. Example
[0033] Example 1 A self-repairing asphalt pavement material, the preparation of which comprises the following steps: S1: Take 22 kg of base asphalt, heat it to 150-180°C, add 15 kg of limestone powder (natural mineral filler), 3 kg of silicate nanoparticles, 9 kg of polyvinylidene fluoride and 100 kg of coarse aggregate in sequence, stir and mix thoroughly to obtain a mixture; S2: 9 kg of the repairable hollow fiber prepared in Preparation Example 1 was added to the mixture and stirred at high speed for 45 min at a stirring speed of 3800 r / min to obtain the self-repairing asphalt pavement material.
[0034] Example 2 A self-repairing asphalt pavement material, the preparation of which comprises the following steps: S1: Take 20 kg of base asphalt, heat it to 150-180°C, add 10 kg of limestone powder (natural mineral filler), 2 kg of silicate nanoparticles, 8 kg of polyvinylidene fluoride and 120 kg of coarse aggregate in sequence, stir and mix thoroughly to obtain a mixture; S2: 10 kg of the repairable hollow fiber prepared in Preparation Example 2 was added to the mixture and stirred at high speed for 60 min at a stirring speed of 3500 r / min to obtain the self-repairing asphalt pavement material.
[0035] Example 3 A self-repairing asphalt pavement material, the preparation of which comprises the following steps: S1: Take 24 kg of base asphalt, heat it to 150-180°C, add 12.5 kg of limestone powder (natural mineral filler), 4 kg of silicate nanoparticles, 10 kg of polyvinylidene fluoride and 80 kg of coarse aggregate, stir and mix well to obtain a mixture; S2: 8 kg of the repairable hollow fiber prepared in Preparation Example 3 was added to the mixture and stirred at high speed for 30 min at a stirring speed of 4000 r / min to obtain the self-repairing asphalt pavement material.
[0036] Example 4 A self-repairing asphalt pavement material, which is different from Example 1 in that the repairable hollow fiber used in this example is prepared by Preparation Example 4.
[0037] Example 5 A self-repairing asphalt pavement material, which is different from Example 1 in that the repairing hollow fiber used in this example is prepared by Preparation Example 5.
[0038] Embodiment 6-8 A self-repairing asphalt pavement material, which is different from Example 1 in that the repairing hollow fibers used in this example are prepared from Preparation Examples 6-8.
[0039] Comparative Example Comparative Example 1 A self-repairing asphalt pavement material, which is different from Example 1 in that no repairing hollow fibers are added in this comparative example.
[0040] Comparative Example 2 A self-repairing asphalt pavement material, which is different from Example 1 in that silicate nanoparticles are not added in this comparative example.
[0041] Performance testing Detection method / test method Compressive strength: Tested in accordance with SH / T 0735-2003 "Asphalt Viscosity Test Method"; Self-healing effect test: standard circular asphalt specimens with a diameter of 25mm and a thickness of 2mm were prepared, and fatigue-repair-fatigue tests were carried out on asphalt materials with different microcapsule contents using an AR1500EX dynamic shear rheometer. In the experiment, the shear load was applied by time scanning control at a 3% strain loading level, the shear loading frequency was 10Hz, and the test temperature was maintained at 80°C. The shear stress was gradually increased until the shear strength of the specimen dropped to 70% of the initial shear modulus, at which time the degree of damage was defined as 30%. Subsequently, the external load was removed, and the material was allowed to self-repair for 6 hours under the same temperature conditions. After the repair was completed, the self-healing property of the asphalt specimen was tested using an improved direct tensile tester. The self-healing efficiency of the material was calculated by comparing the shear strength before and after the repair, and the ratio of the shear strength before and after the repair; Thermal stability: The Marshall stability test was carried out in accordance with the "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG / E20-2011). The MTS universal testing machine was used to conduct a four-point bending fatigue test, with the complete fracture of the asphalt pavement material as the failure standard, to test the thermal stability of the asphalt pavement material. Aging resistance test: The prepared asphalt pavement material specimens with a size of 50×50×200mm were placed in a UV accelerated aging test box and exposed to a UV accelerated aging device. The aging time was set to 720h to simulate the light and oxidation effects in the natural environment. The compressive strength of the material before and after aging was tested to reflect the impact of aging on material performance.
[0042] Table 1 Test data Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the experimental data of Examples 1-3 are all higher than those of Comparative Example 1, indicating that the addition of the repairable hollow fiber significantly improves the various properties of the self-repairing asphalt pavement material. The repairable hollow fiber can not only enhance the overall strength of the material, but also release the repair agent to self-repair when cracks appear in the material, thereby improving the durability and service life of the material.
[0043] Combining Examples 1-3 and Comparative Example 2 and Table 1, it can be seen that the experimental data of Examples 1-3 are all higher than those of Comparative Example 2, indicating that the addition of silicate nanoparticles plays an important role in improving the performance of self-repairing asphalt pavement materials. Silicate nanoparticles improve the overall performance of the material by enhancing the interaction force within the material, increasing the density of the material, and reducing the formation of cracks.
[0044] Combining Example 1 with Example 4 and Table 1, it can be seen that various experimental data of Example 1 are better than those of Example 4, especially in the thermal stability performance test. This shows that the use of polyvinyl butyral and poly(hexamethylene terephthalamide) as the wall material of the hollow fiber can soften and release the repair agent at high temperature, and re-harden after cooling, providing good temperature responsiveness, which significantly improves the thermal stability and self-healing efficiency of the material.
[0045] Combining Example 1 with Example 5 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 5. When the dithiol compound is not added, although the repair agent can be released and repaired after the material is damaged, the fiber shape cannot be completely restored, resulting in the mechanical properties of the repaired material being inferior to those of the material with the dithiol compound added.
[0046] Combining Example 1 with Examples 6-8 and Table 1, it can be seen that the experimental data of Examples 6-8 are better than those of Example 1, indicating that the addition of nano-silicon dioxide can improve the overall performance of the material by filling the tiny pores inside the material, enhancing the interaction force inside the material and increasing the density of the material.
[0047] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A self-repairing asphalt pavement material, characterized in that: The composition comprises the following raw materials in parts by weight: 20-24 parts of matrix asphalt, 8-10 parts of repair hollow fibers, 2-4 parts of silicate nanoparticles, 10-15 parts of natural mineral fillers, 8-10 parts of polyvinylidene fluoride, and 80-120 parts of coarse aggregate.
2. The self-repairing asphalt pavement material according to claim 1, characterized in that: The repairable hollow fiber uses polyvinyl butyral and polyhexamethylene terephthalamide as wall materials and an asphalt repair agent as core material, and is obtained through a dry-wet spinning process.
3. The self-repairing asphalt pavement material according to claim 2, characterized in that: The preparation of the repaired hollow fiber comprises the following steps: (1) Put polyvinyl butyral into dichloromethane solvent and stir to dissolve, add dithiol compound to the above solution and continue to stir until it is evenly dispersed, add poly(hexamethylene terephthalamide) solution pre-dissolved in dimethylformamide and stir evenly, place in a vacuum oven at 55-65°C and stand for defoaming for 22-24 hours to obtain a casting solution; (2) The casting liquid is extruded and spun under the action of high-pressure nitrogen to form a hollow fiber shape. During this process, the asphalt repair agent is pressurized into the cavity of the hollow fiber as an internal coagulation liquid to serve as a support, and the fiber end is sealed. It is then immersed in water to coagulate and form, and after drying, a repaired hollow fiber with a length of 2-3 cm is formed.
4. A self-repairing asphalt pavement material according to claim 2 or 3, characterized in that: The preparation process of the repairable hollow fiber includes the following raw materials in parts by weight: 6-8 parts of polyvinyl butyral, 18-20 parts of dichloromethane solvent, 0.5-2 parts of dithiol compound, 14-16 parts of polyhexamethylene terephthalamide solution, and 16-20 parts of asphalt repair agent.
5. The self-repairing asphalt pavement material according to claim 4, characterized in that: 0.5-3 parts of nano silicon dioxide are also added into the repaired hollow fiber.
6. The self-repairing asphalt pavement material according to claim 2, characterized in that: The asphalt repair agent comprises 8-10 parts of waterborne epoxy resin, 60-70 parts of solvent oil and 10-15 parts of carboxyl styrene butadiene latex.
7. The self-repairing asphalt pavement material according to claim 1, characterized in that: The natural mineral filler is limestone powder.
8. A method for preparing the self-repairing asphalt pavement material according to any one of claims 1 to 7, characterized in that: The steps include: S1: heating the base asphalt to 150-180° C., adding the natural mineral filler, silicate nanoparticles, polyvinylidene fluoride and coarse aggregate, stirring and mixing well to obtain a mixture; S2: Add the repairable hollow fiber into the mixture and stir it at high speed for 30-60 minutes at a stirring speed of 3500-4000 r / min to obtain the self-repairing asphalt pavement material.